ChemInform Abstract: Photochemical Double 5‐exo Cyclization of Alkenyl‐Substituted Dithienylacetylenes: Efficient Synthesis of Diarylated Dithienofulvalenes. Issue 8 (25th February 2014) - Fukazawa, Aiko; Karasawa, Takashi; Zhang, Hongyu; Minemura, Kazumitsu; Camacho, Cristopher; Wang, Jian; Irle, Stephan; Yamaguchi, Shigehiro
Abstract A new photochemical cyclization of bis(alkenylthienyl)acetylenes (I) is presented as an efficient method to synthesize diaryl‐substituted dithienofulvalenes (II).